An umbrella review of meta-analyses on diagnostic accuracy of C-reactive protein. (August 2022) - Yang, Qiuyu; Li, Mengting; Cao, Xiao; Lu, Yao; Tian, Chen; Sun, Mingyao; Lai, Honghao; Tian, Jinhui; Li, Jiang; Ge, Long
Abstract: Background: Multiple studies and meta-analyses have reported the diagnostic value of C-reactive protein (CRP) in several diseases. However, the precision, and influence of potential bias regarding the diagnostic values of existing evidence may have implications for clinical practice. Methods: We performed an umbrella review of diagnostic test accuracy studies of CRP for diseases by searching PubMed, Embase, China National Knowledge Infrastructure, and WanFang databases up to March 7, 2021. Five independent reviewers evaluated eligibility, extracted data, and assessed methodological quality. We descriptively analyzed the diagnostic accuracy of CRP for multiple diseases, heterogeneity between studies, and publication bias. Results: Seventy-four meta-analyses were included, with 13 diseases classified according to the International Classification of Diseases-11 (ICD-11). The methodological quality of the included meta-analyses was mostly low, with only 16 meta-analyses rated as moderate or high, including seven diseases classified by ICD-11. CRP had a relatively greater diagnostic accuracy for two of these diseases. For postoperative infectious complications after bariatric surgery, sensitivity and specificity were 0.81 (0.34–1) and 0.91 (0.73–1), respectively. For anastomotic leakage after colorectal surgery, sensitivity and specificity were 0.95 (0.75–0.99) and 0.95 (0.75–0.99), respectively. Conclusions: The diagnostic accuracy of CRP for multiple diseases has been extensively studied; however, most studies have low methodological quality. Evidence indicates that CRP has a relatively greater diagnostic accuracy for inflammation and infection diseases, especially for postoperative infectious complications after bariatric surgery and anastomotic leakage after colorectal surgery. Highlights: The umbrella review provides a landscape of the existing meta-analyses on diagnostic values of CRP. CRP has a relatively greater diagnostic accuracy for postoperative infectious complications after bariatric surgery and anastomotic leakage after colorectal surgery. This finding may help rule out early postoperative infectious complications for patients after bariatric and colorectal surgery and may be helpful for a safe early hospital discharge.